Mirrors of narrative in contemporary Arabic poetry: "the modernity of the self and its resonance" - Bouhraoua, Hebib (The International tax journal, 2026)
This research paper deals with "narrative mirrors in Arabic poetry: the modernity of the self and its resonance", to highlight the role of narrative as an expressive mechanism in contemporary Arab poetry. She also discusses the relationship between narrative and self-expression, explaining how Arabic poetry reflects the resonance of the individual and collective self in the time of modernity. It focuses on the role of narrative in conveying contemporary human experience, and the consequent interweaving of the psychological and social dimension of the poetic text. The main objective of this research paper is to provide a deeper understanding of the manifestations of modernity in Arabic poetry through narrative, and to highlight the impact of this employment on the structure of poetic texts and their expression of self-issues.